WORLD AGE GROUP COMPETITIONS (WAGC) AS A DEVELOPMENT PILLAR FOR TRAMPOLINE GYMNASTICS: ANALYSING NATIONAL FEDERATIONS' RESULTS BETWEEN 1999 AND 2019 - Miguel Vicente-Mariño (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Trampoline Gymnastics is a consolidated sport within the gymnastics family. Since the International Trampoline Federation (FIT) and the International Gymnastics Federation (FIG) merged in 1999, the growth and expansion of Trampoline Gymnastics have remained constant. In this process, the role played by the World Age Group Competitions (WAGC) is worth to be mentioned, as this event has been established as the main entrance pathway to any gymnast or national federation willing to reach the international elite level. The first edition of these competitions dates back to 1973 in London, and the 27th took place in Tokyo in November 2019. This article aims to explain the key role played by WAGC in the evolution and consolidation of this Olympic sport, by conducting an in-depth analysis of the participation data and medal distribution during the last fourteen editions, all the ones taking place under the FIG umbrella. In order to complete a broader picture of these competitions, a detailed analysis in terms of editions, gender and disciplines is presented. Results return a clear dominance of the Russian Federation national team and a group of international contenders that built up their strong presence at the international scene on top of a constant and well-planned strategy in WAGC. These events have achieved to become part of the sports' internal culture and the education system has incorporated them into all the recommended procedures at the international level.